CURRENT AUDITING PROBLEMS. - Bailey, George D. (The Accounting Review, 1950)
Abstract According to the author one will note that he avoided many current professional auditing problems. There are quite a number of these that are interesting which may be mentioned even though he had elected not to discuss them. The teaching of accounting and auditing has come a very long way since the author studied the two subjects in a course in commerce in his university days. In his case, there is a span of forty years of contact with the teaching of accounting. He thinks the teaching has more than kept pace with the development of the profession, and it has contributed immeasurably to the success of the profession. The development of the collegiate courses in accounting and auditing is not in the hands of the practical practicing accountants, but properly it is dependent upon the wisdom of the professional educators. In his opinion, the profession can have complete confidence that the teaching of accounting will keep pace with the needs of the profession. According to the author the profession is not satisfied that it has reached proper standards of disclosure. At the present time, the desires of the public for more information clash with the desires of management to disclose no information that will be competitively harmful or, by increasing the problems of management, are harmful to the owners of the business.